Melanized meristematic mutant of Fonsecaea monophora promotes macrophage apoptosis - Minying LI; Huan HUANG; Hongfang LIU; Weiying ZENG; Liyan XI (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Objective To explore the effect of Fonsecaea monophora (F.monophora) pigment strain melanin on the apoptosis of macrophages RAW264.7. Methods Macrophages were co-cultured with PBS, F.monophora pigment strain and albino strain, Western blot was used to detect the expression of PARP-1; and real-time quantitative PCR was used to detect the expression of BCL-2 and BAX in each group. Annexin V FITC fluorescent staining was used to detect apoptosis. Results After co-cultured with macrophages RAW264.7, the pigmented strain was more capable of cutting PARP-1, down-regulating the ratio of BCL-2/BAX expression, and up-regulating Annexin V FITC positive cells than the albino strain. Conclusion The F.monophora pigment strain may resist the immune killing effect of macrophages by promoting the apoptosis of macrophages, while the albino strains cannot obviously promote the apoptosis of macrophages.